ІНТЕРАКТИВНІ ТЕХНОЛОГІЇ: ДИДАКТИЧНІ УМОВИ ЗАСТОСУВАННЯ ДЛЯ ПІДГОТОВКИ МАЙБУТНІХ УЧИТЕЛІВ (Педагогіка вищої та середньої школи, 2008)
The article deals with the problems of introduction of interactive technologies into the educational process. The attempt to substantiate the system of didactic conditions of interactive technologies effective use in future teachers ’ training has been made.